Sistem Monitoring Kendaraan Secara 3D dengan Sensor Tekanan Udara dan Global Positioning System (GPS) Berbasis Web Secara Realtime - Fatkhur Rohman; Jatmiko Endro Suseno; Catur Edi Widodo (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
A research on telemetry or remote measurement has been conduced, for the parameters of the position of a moving object, ie the vehicle. Parameters such as latitude and longitude position is obtained from the GPS receiver (Global Positioning System). GPS receiver is used Ublox Noe 6 M. In addition it’s also added a altitude parameter, which is obtained by converting the changes of air pressure. Sensor BMP180 used to measure air pressure. Both of these devices are read and controlled by a microcontroller ATmega328 with the Arduino software. The GPS receiver to get latitude and longitude coordinates from the satellite. Coodinates data is sent to a microcontroller, combined with altitide data, then data sent to the database server using internet with GSM network. In this system used web interface that allows users to monitor the position of the vehicle, without necessary for special receiving station. Based on the results of validation latitude and longitude coordinates from the GPS receiver, with GARMIN GPS devices with the GPSMAP 78s series, this GPS receiver has the highest standart deviation ± 0.000006 degrees for the longitude and ± 0.000012 for latitude. The position of the vehicle in form of latitude and longitude coordinates, then illustrated on Google Maps. The results of this study, acqusition system that has been mounted on the vehicle position coordinates can transmit data to the server, and the data transmission process becomes faster and cheaper. This system will continue sends the data for vehicles that are in the area covered by the GSM network provider. Lack of this system is data transmission medium that is highly dependent on the availability of the GSM network. If the GSM network is weak, it can cause failures in data transmission.